The 4Ps Impact On Purchase Decision using Logistic Reggression: A Case Of Rabbani Muslim Fashion in Bandung, Indonesia - Sussy Susanti, Yunia Mulyani Azis, Siti Nuraisyah (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This research is based on the decrease in the number of consumers do transaction of buying Muslim Rabbani fashion products within the period 2013-2015. The decline in the number of consumers who do this transaction indicates the existence of a declination in the Purchasing Decision of Muslim fashion products Rabbani, so it can be formulated in this research that how consumers form buying decisions amidst increasingly tight competition of Muslim clothing products, the rise of new brands and more qualified, based on the Marketing Mix perspective. The purpose of this research is to analyze the influence of Marketing Mix (4Ps) on Purchasing Decision on Rabbani product. This research uses descriptive and verifikatif method. Data were collected by questionnaire and interview technique. The sample used in this study is 100 men and women who respondents who wear Muslim dress in the city of Bandung. The method of analysis used in this research is Logistic Regression Analysis. The results of this research indicate that Marketing Mix (4Ps) has a significant influence, either partially or simultaneously to the purchase decision. The dimension of Marketing Mix partially that has the greatest influence is Product, while the smallest influence is shown by Place.